Study of Organizational Citizenship Behaviour and Justice of Employees in a Few Select Public and Private Sector Banks in Chandigarh - Kaur, Rupinder (Prabandhan: Indian Journal of Management, 2011)
The purpose of the paper was to determine the perception of employees' organizational citizenship behaviour and justice among private and government banks. The study also aimed to determine whether such perceptions vary, depending on the variables of gender and work experience. Data was collected from 122 employees working in private and government sector banks at Chandigarh. Organizational justice was measured on the scale given by Niehoff&Moorman (1993) and Organizational citizenship behaviour was measured on the scale given by Podsakoff, Mackenzie, Moorman&Fetter (2000). The analysis of data was done by using non - parametric tests. The results indicated that there was no difference in the employees' perception of organizational citizenship behaviour in both private and government banks, whereas, the employees of government banks had a more positive perception of organizational justice than employees of private banks. There was a moderate positive relationship between organizational justice and citizenship behaviour of employees.